Soil physical properties and yield of soybean and corn grown with wastewater - Alexsandro C. dos S. Almeida; Higor H. O. Santos; Dhiego P. Bortolo; Elaine R. P. Lourente; Jorge W. Cortez; Fabricio C. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate soybean and corn yields and soil physical attributes of a Dystrophic Red Latosol fertilized with swine wastewater (SW). Therefore, a field experiment was conducted in randomized blocks to evaluate five treatments of fertilization in the 2014/2015 season (soybean in the summer and corn in the second season). The treatments were: T1 - control (fertilized exclusively with chemical fertilizers); T2 - fertilized with 1270 m3 ha-1 of SW; T3 - fertilized with 170 m3 ha-1 of SW; T4 - fertilized with 50 m3 ha-1 of SW; and T5 - fertilized with 50 m3 ha-1 of SW + chemical fertilization. Soil samplings and soil physical analyses were performed before soybean cultivation and after corn harvest. No significant alteration was observed in soil physical attributes during the evaluation period. The application of swine wastewater in the fertilization of soybean and corn, cultivated in Dystrophic Red Latosol with high clay contents, positively affected these crops, since it led to good yields in soybean (with an average of 2990.85 kg ha-1) and increased corn yields (with a maximum of 7126.5 kg ha-1). In addition, soil physical properties were not altered.